1997
DOI: 10.1002/(sici)1096-8628(19970414)69:4<370::aid-ajmg7>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Coloboma, mental retardation, hypogonadism, and obesity: Critical review of the so-called Biemond syndrome type 2, updated nosology, and delineation of three “new” syndromes

Abstract: Biemond syndrome type 2 (BS2) is classically regarded as a recessively inherited condition (MIM 210350) comprising mental retardation, coloboma, obesity, polydactyly, hypogonadism, hydrocephalus, and facial dysostosis. Clinically, the disorder is closely related to Bardet-Biedl syndrome. Few cases have been reported, most of them before 1970. We present clinical data on three mentally retarded sporadic cases with coloboma, obesity, and hypogenitalism (in two of them), fitting as first glance a diagnosis of BS2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 25 publications
1
9
0
1
Order By: Relevance
“…Our three cases of genetic obesity, associated with hexadactyly and other clinical abnormalities, were diagnosed as familial cases of BBS, thus excluding other forms of genetic obesity characterized by different main features (such as hearing disorders, coloboma, hypotonia, characteristic facies or facial dysostosis, ataxia, spastic paraplegia, etc.) [96–107]. Our patients presented all the well‐recognized features of BBS [4,10–15,25,28], i.e.…”
Section: Literature Review and Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Our three cases of genetic obesity, associated with hexadactyly and other clinical abnormalities, were diagnosed as familial cases of BBS, thus excluding other forms of genetic obesity characterized by different main features (such as hearing disorders, coloboma, hypotonia, characteristic facies or facial dysostosis, ataxia, spastic paraplegia, etc.) [96–107]. Our patients presented all the well‐recognized features of BBS [4,10–15,25,28], i.e.…”
Section: Literature Review and Discussionsupporting
confidence: 54%
“…Differential diagnosis is important because certain syndromes, consisting of ocular and/or auditory defects, mental retardation, genitalia hypoplasia, genetic obesity and digital anomalies (with and without ocular impairment from retinal dystrophy), can be misdiagnosed as BBS, from which, in fact, they should be carefully differentiated [28,96–107]. These syndromes related to BBS are presented in Table 3.…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…Bremond-Gignac et al (47) described WAGRO syndrome (WAGR + Obesity); this may be attributed to the deletion of an obesity gene. Aniridia combined with zonular cataract and polydactyly was also explained in a patient with Bardet-Biedl syndrome by Verloes et al (48). Electroretinograms (ERGs) performed by Tremblay et al (49) for patients with aniridia, revealed definite retinal dysfunction, although its etiology is not yet clear.…”
Section: Resultsmentioning
confidence: 99%
“…The dominant model assumes the effects of the two disease-allele carrying genotypes AA and AB are the same (AA = AB) and different from that of the BB genotype. An example is the coloboma-obesity-hypogenitalism-mental retardation syndrome 45. In the recessive model, the genotypic effects of BB and AB are assumed to be the same and different from that of the AA genotype.…”
Section: Methodsmentioning
confidence: 99%